0158 Mental health simulation training: The bigger picture – why it's needed nationally. (2nd November 2015) - Fernando, Asanga; Cross, Sean
Abstract : Context: More integrated mental healthcare is one of the key messages of the NHS five year forward view. 1 The government's mandate to Health Education England 2 highlights the need for greater, more effective mental health training, urging organisations to improve mental health awareness as well as urging effective investment in training for healthcare professionals managing comorbidity. The national shape of training report, 3 also endorses this. Looking beyond healthcare, Henderson and Madan 4 report that mental illness costs the UK economy up to £70 billion annually, and is now the leading cause of sickness absence. 5 The chief medical officer's annual report, 6 acknowledges the growing problems mental health related lost workforce productivity. Mental health simulation training has been shown to improve knowledge, attitudes, confidence, technical and non-technical skills. 7, 8 We feel that a national mental health simulation strategy is needed to bridge the gap between policy and training. Methodology: Focus groups will take place with a diverse range of stakeholders including business and HR management, healthcare professionals, patients, carers, simulation training providers, voluntary sector organisations, education providers and policy makers, as well as medical and nursing professional bodies. There will be a thematic analysis of the focus groups, exploring the utility of simulation and other experiential learning interventions in addressing these recommendations. Results: Thematic analysis of the focus groups will be generated, published and presented. This will be used to guide the development of a collaborative steering strategy group will be formed from individuals and organisations who are keen to address this gap, using the themes identified as priorities. Conclusions: Addressing effective training in mental health is a national priority. This study aims to establish a national strategy for the role of simulation in doing so, in a collaborative and relevant manner. References: NHS England Five Year Forward View, 2014 Delivering high quality, effective, compassionate care: 2014. A mandate from the Government to Health Education England. https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/310170/DH_HEE_Mandate.pdf Securing the future of excellent patient care Final report of the independent review Led by Prof D Greenaway. http://www.shapeoftraining.co.uk/static/documents/content/Shape_of_training_FINAL_Report.pdf_53977887.pdf Henderson M, Madan I, Hotopf M. Work and mental health in the UK. BMJ 2014:348 Sainsbury Centre for Mental Health. Mental health at work: developing the business case. London, 2007 Annual Report of the Chief Medical Officer. Public Mental Health Priorities – investing in the evidence, 2013 Doolen J, et al . An evaluation of mental health simulation with standardized patients. Int J Nurs Educ Scholarsh 2014;11(1):1–8 Thomson AB, Cross S, Key S, Jaye P, Iversen AC. How we developed an emergency psychiatry training course for new residents using principles of high-fidelity simulation. Med Teach 2013;35(10):797–800